Novel Fermented Grain-Based Products - Emerald M.; Rajauria G.; Kumar V. (My University, 2025)
Fermentation of grains is an ancient method which helps increase the nutritional value and digestibility of grains, protects stomach from the harmful pathogens, improving absorption of bioactive molecules and minerals though the intestinal tract synergistically balancing the gut microbiota. Fermentation of grains is crucial for the bread manufacturing and producing a variety of beverages and nutritional drinks. The type of the grain substrate, methods of fermentation and type of the microorganisms involved into the fermentation process vary depends on geographical region and historical traditions. Grains fermentation process is used for production of ethanol, biofuel, enzymes and intermediates, micronutrients and amino acids, flavours and masking volatiles. This chapter is dedicated to an importance of the grain fermentation for the balanced and nourishing food, beverages and animal feeds. © 2016, Springer International Publishing Switzerland.